Measurement of Earth Value Using Earth Tester Measurement at Efarina University - Charla Tri Selda Manik (Journal of Science Technology (JoSTec), 2020)
Grounding refers to the connection of an electrical equipment or installation to the ground so that it can protect humans from electric shock , and secure installation components from the danger of abnormal current voltages . This grounding system has low resistance properties, so that the overcurrent in the installation network can be flowed quickly to the ground to minimize damage to equipment in the building and protect the people inside. This study reviews the measurement of grounding around the earth at the efarina university. To find out the condition of the grounding resistance at each grounding, it is necessary to measure each grounding by measuring directly on the grounding installation network using an earth tester using an electrode pin. The calculation of grounding resistance is based on the type of soil, the depth of the electrode rod. The results show that the earth around the campus lobby has met the General Electrical Installation Requirements (PUIL) standard, which is smaller than 5 ohms. However, for earthing around the health faculty, it does not meet the PUIL standard, which is less than 5 ohms.